PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBASIS PERMAINAN SHUFFLE AND RECALL PADA MATERI SISTEM PENCERNAAN UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN HASIL BELAJAR SISWA SMP - Novela Pramudya, Vinda; Puspitarini, Sapti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of the Teams Games Tournament (TGT) cooperative learning model in improving students’ learning outcomes and social skills. The primary issue addressed is the low level of active participation and academic achievement in the digestive system curriculum. Using a pre-experimental design with a One-Group Pretest-Posttest design, this study involved 32 eighth-grade students from Class VIII-G at SMP Negeri 2 Krian as the subjects of observation. The social skills measured included cooperation, assertiveness, responsibility, and friendliness. Data were collected to determine the extent to which the TGT model, integrated with the “shuffle and recall” game, could alter classroom dynamics and students’ cognitive achievements. The results of the analysis show that this model is significantly effective in improving learning outcomes, with N-Gain results indicating that 59% of students achieved the high category and 41% fell into the moderate category. Additionally, there was an improvement in students’ social skills, moving from the good category to the very good category. The entire instructional sequence was implemented optimally and received a very positive response from the students. Thus, this game-based TGT model has proven effective as a solution for enhancing both students’ academic competencies and social skills in the digestive system curriculum.